PAPAN INFORMASI DIGITAL DINAMIS BERBASIS ATMEGA 8535 DENGAN MEDIA PERANTARA BLUETOOTH DI LABORATURIUM HADWARE UNIVERSITAS DEHASEN BENGKULU - Hesti Yupita Sari; Prama Wira Ginta; Yanolanda Suzantri H (Jurnal Media Infotama, 2015)
From the results of this research is that the information board can provide information using android phone by sending a character letter A or B. This information boards can be controlled with an application board computer information, and could work without komputer. The purpose of making the information board Dehasen Bengkulu University aims to facilitate providing information to students in the laboratory hardware Dehasen University of Bengkulu.Keywords: Board, Information, Unived, Bengkulu.